2018
DOI: 10.1111/ina.12503
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of outdoor and indoor PM2.5collected during haze events: Transformations and modified source contributions resulting from outdoor-to-indoor transport

Abstract: Changes in the chemical constitution and sources of ambient PM following the infiltration of air into indoor environments were investigated. We collected PM samples from air inside and outside 31 rooms in Beijing residences during hazy episodes. We calculated the indoor-to-outdoor ratios and the correction (k ) of each infiltration factor for each chemical component of PM to determine the effects of infiltrative behavior. The outdoor and indoor mass concentrations of PM during the sampling period were 70-460 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 83 publications
(207 reference statements)
0
15
0
Order By: Relevance
“…Twenty papers reported HPLs in the living rooms, 14 papers in the bedrooms, and 17 papers in the kitchens. General information of studies included for the final analysis 13,28‐89 was listed in Table S2.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty papers reported HPLs in the living rooms, 14 papers in the bedrooms, and 17 papers in the kitchens. General information of studies included for the final analysis 13,28‐89 was listed in Table S2.…”
Section: Methodsmentioning
confidence: 99%
“…Ca 2+ is also able to elicit the expression of the ATP-binding cassette subfamily C member 3 (ABCC3), a promoter of Twist and EMT in breast cancer cells (Stewart et al, 2015). As Ca 2+ has been well characterized as one of the most plentiful cations in PM 2.5 , and PM 2.5 is able to penetrate into the bloodstream or be taken by cells, PM 2.5 exposure might result in increased Ca 2+ concentration in microenvironment around the epithelia or cytoplasm, which could further regulate the activity of pro-EMT Ca 2+ signaling (Huang et al, 2018; Qin et al, 2018; Xie and Zhao, 2018). In our recent study, pulmonary epithelial cells showed EMT-like phenotype after long-term low dose PM2.5 exposure, and a subset of the intracellular differentially expressed genes was significantly related to the cellular response to calcium ion (Xu et al, 2019b).…”
Section: Potential Mechanisms Of Pm25-induced Epithelial-mesenchymalmentioning
confidence: 99%
“…PM 2.5 compositions have been suggested to play a causative role in these adverse health effects . Nitrate (NO 3 − ) and ammonium (NH 4 + ) are inorganic constituents of PM 2.5 that can constitute 20% or more of total ambient PM 2.5 dry mass . These ions have also been consistently correlated with adverse health effects in epidemiology studies .…”
Section: Introductionmentioning
confidence: 99%